Squaring the circle of healthcare supplies. Issue 2 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to use a systems lens to assess the comparative performance of healthcare supply chains and provide guidance for their improvement.Design/methodology/approach – A well‐established and rigorous multi‐method audit methodology, based on the uncertainty circle model, yields an objective assessment of value stream performance in eight Australasian public sector hospitals. Cause‐effect analysis identifies the major barriers to achieving smooth, seamless flows. Potentially high‐leverage remedial actions identified using systems thinking are examined with the aid of an exemplar case.Findings – The majority of the healthcare value streams studied are underperforming compared with those in the European automotive industry. Every public hospital appears to be caught in the grip of vicious circles of system uncertainty, in large part being caused by problems of their own making. The single exception is making good progress towards seamless functional integration, which has been achieved by elevating supply chain management to a core competence; having a clearly articulated supply chain vision; adopting a systems approach; and, managing supplies with accurate information.Research limitations/implications – The small number of cases limits the generalisability of the findings at this time.Practical implications – Hospital supply chain managers endeavouring to achieve smooth and seamless supply flows should attempt to elevate the status of supplies management within their organisation to that of a core competence, and should use accurate information to manage their value streams holistically as a set of interwoven processes. A four‐level prism model is proposed as a useful framework for thus improving healthcare supply delivery systems.Originality/value – Material flow concepts originally developed to provide objective assessments of value stream performance in commercial settings are adapted for use in a healthcare setting. The ability to identify exemplar organisations via a context‐free uncertainty measure, and to use systems thinking to identify high‐leverage solutions, supports the transfer of appropriate best practices even between organisations in dissimilar business and economic settings. Acknowledgements : The authors would like to thank all eight participating hospitals and their affiliated employees. The insight you provided is highly appreciated.